138k views
5 votes
How do I solve for x here? Use the properties of logarithms to find a value for x. Assume a,b, and M are constants.


ln(a*b^(x)) = M

The answer in the back of the textbook is
x=(M-ln(a))/(ln(b))

But I am unsure how to get to that solution. Do I start with ln(a) + ln(b)^x?

User Amquack
by
5.6k points

1 Answer

5 votes

Yes, you're right! The first step is rewriting the equation as


\ln(a) + \ln(b^x) = M

Subtract
\ln(a) from both sides:


\ln(b^x) = M-\ln(a)

Use the property
\ln(a^b) = b\ln(a) to rewrite the equation as


x\ln(b) = M-\ln(a)

Divide both sides by
\ln(b)


x = (M-\ln(a))/(\ln(b))

Alternative strategy:

Consider both sides as exponents of e:


e^(\ln(ab^x)) = e^M

Use
e^(\ln(x)) = x to write


ab^x = e^M

Divide both sides by a:


b^x = (e^M)/(a)

Consider the logarithm base b of both sides:


x = \log_b\left((e^M)/(a)\right)

The two numbers are the same: you can check it using the rule for changing the base of logarithms

User Wombleton
by
4.9k points